Waves in asymmetric hyperbolic media - Hashemi, S. M.; Nefedov, I.S.; Soleimani, M. (Photonics Letters of Poland, 2013)
In this paper, a homogenization model is applied for analysis of the spectrum of natural modes in s finite-thickness slab of tilted metallic carbon nanotubes. Tilted anisotropy axis causes a difference between normal wave vector components for waves, propagating upward and downward with respect to slab interfaces. This asymmetry effects becomes very strong for hyperbolic media and it results in appearance of backward waves and accumulation points in spectra of natural waves. Full Text: PDF References D. R. Smith and D. Schurig, "Electromagnetic Wave Propagation in Media with Indefinite Permittivity and Permeability Tensors", Phys. Rev. Lett. 90, 077405 (2003). CrossRef P. A. Belov, et al., "Strong spatial dispersion in wire media in the very large wavelength limit", Phys. Rev. B 67, 113103 (2003). CrossRef I. S. Nefedov, "Electromagnetic waves propagating in a periodic array of parallel metallic carbon nanotubes", Phys. Rev. B 82, 155423 (2010). CrossRef Z. Jakob, I. Smolyaniniv, and E.E. Narimanov, "Broadband Purcell effect: Radiative decay engineering with metamaterials", Appl. Phys. Lett. 100, 181105 (2012). CrossRef N. Poddubny, et al., "Microscopic model of Purcell enhancement in hyperbolic metamaterials", Phys. Rev. B 86, 035148 (2012). CrossRef V. N. Ivanov, et al., "Waves in a tangentially magnetized ferrite layer (electrodynamic calculation and uniform asymptotes)", Izvestiya Vysshikh Uchebnikh Zavedenii Radiofizika (Radiophysics and Quantum Electronics), 32, 764 (1989). CrossRef A. Yakovlev, et al., "Characterization of Surface-Wave and Leaky-Wave Propagation on Wire-Medium Slabs and Mushroom Structures Based on Local and Nonlocal Homogenization Models", IEEE Trans. Microw. Theory Tech. 57, 2700 (2009). CrossRef I. S. Nefedov and S. A. Tretyakov, "Ultrabroadband electromagnetically indefinite medium formed by aligned carbon nanotubes", Phys. Rev. B 84, 113410 (2011). CrossRef I. S. Nefedov and C. R. Simovski, "Giant radiation heat transfer through micron gaps", Phis. Rev. B 84, 195459 (2011). CrossRef S.-A. Biehs, M. Tschikin, and P. Ben-Abdallah, "Hyperbolic Metamaterials as an Analog of a Blackbody in the Near Field", Phys. Rev. Lett. 109, 104301 (2012). CrossRef Yu Guo, C. L. Cortes, S. Molesky, and Z. Jacob, "Broadband super-Planckian thermal emission from hyperbolic metamaterials", Appl. Phys. Lett. 101, 131106 (2012). CrossRef S.-A. Biehs, M. Tschikin, R. Messina and P. Ben-Abdallah, "Super-Planckian near-field thermal emission with phonon-polaritonic hyperbolic metamaterials", Appl. Phys. Lett. 102, 131106 (2013). CrossRef B. Liu and S. Shen, "Broadband near-field radiative thermal emitter/absorber based on hyperbolic metamaterials: Direct numerical simulation by the Wiener chaos expansion method", Phys. Rev. B 87, 115403 (2013). CrossRef G. Y. Slepyan, S. A. Maksimenko, A. Lakhtakia, O. Yevtushenko, A.V. Gusakov, "Electrodynamics of carbon nanotubes: Dynamic conductivity, impedance boundary conditions, and surface wave propagation", Phys. Rev. B 60, 17136 (1999). CrossRef S. M. Hashemi and I. S. Nefedov, "Wideband perfect absorption in arrays of tilted carbon nanotubes", Phys. Rev. B 86 195411 (2012). CrossRef